Gender differences in cardiac ischemic injury and protection--experimental aspects - Ostadal, Bohuslav; Netuka, Ivan; Maly, Jiri; Besik, Josef; Ostadalova, Ivana (Experimental biology and medicine (Maywood, N.J.), 2009)
This review summarizes some available information on gender differences of myocardial injury with particular attention to experimental approach. It has been observed that significant gender differences exist already in normal heart. They involve among others cardiac growth, contractile function, calcium metabolism and function of mitochondria. Differences, characteristic of the normal myocardium, generate the logical presumption of the different reaction of the male and female heart to various pathogenic factors. Most of the experimental studies confirm the clinical observations: increased resistance of the female heart to ischemia/reperfusion injury was shown in dogs, rats, mice and rabbits. Furthermore, gender differences in the ischemic tolerance of the adult myocardium can be influenced by interventions (e.g. hypoxia) imposed during the early phases of ontogenetic development. The already high tolerance of the adult female heart can be increased by adaptation to chronic hypoxia and ischemic preconditioning. It seems that the protective effect depends on age: it was absent in young, highly tolerant heart but it appeared with the decrease of natural resistance during aging. Both experimental and clinical studies have indicated that female gender influences favorably also the remodeling and the adaptive response to myocardial infarction. It follows from the data available that male and female heart differs significantly in many parameters under both physiological and pathological conditions. Detailed molecular and cellular mechanisms of these differences are still unknown; they involve genomic and non-genomic effects of sex steroid hormones, particularly the most frequently studied estrogens. The cardiovascular system is, however, influenced not only by estrogens but also by other sex hormones, e.g. androgens. Moreover, steroid hormone receptors do not act alone but interact with a broad array of co-regulatory proteins to alter transcription. The differences are so important that they deserve serious consideration in clinical practice in search for proper diagnostic and therapeutic procedures.
Keywords: reperfuzní poškození myokardu; Male; Dogs; srdce; sexuální faktory; Myocardial Reperfusion Injury; mužské pohlaví; králíci; krysa rodu Rattus; Animals; lidé; ženské pohlaví; Humans; zvířata; Sex Factors; Rats; Rabbits; myši; psi; Mice; Female; Heart